PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP PENGAMBILAN KEPUTUSAN INVESTOR DALAM SIKLUS HIDUP PERUSAHAAN YANG BERBEDA - Laksmi Nitya Pradipta; Elizabeth Lucky Maretha Sitinjak; Y. Wisnu Djati Sasmito (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
In this study will show the decision of investors at each stage of the life cycle has consideration of different financial ratios. The purpose of the study is to determine the effect of the company's financial performance on investor decision making at the five stages of the company's life cycle. The study uses data of manufacturing companies in the 2014-2016 period. The analysis was performed by SPSS analysis tool. The result is ratio that affects investor decision making in each cycle is different. In the introduction stage only liquidity ratios affect the decision making of investors with a positive direction. At the growth stage, leverage ratios that influence investor decision-making in a negative direction and activity ratio in a negative direction. The shakeout phase is only the liquidity ratio that influences the decision making of investors in a positive direction. The mature stage, the profitability ratio that influences the decision making of investors with a positive direction, the liquidity ratio influences in the negative direction and the leverage ratio influences the positive direction. In the decline stage which influences investor decision making is the leverage ratio in the negative direction while the liquidity ratio and activity ratio have a positive direction.